Histologic Diagnosis of Inflammatory Bowel Diseases. (January 2022) - Kővári, Bence; Báthori, Ágnes; Friedman, Mark S.; Lauwers, Gregory Y.
Abstract : Inflammatory bowel disease, including ulcerative colitis and Crohn disease, is an idiopathic chronic inflammatory condition of the gastrointestinal tract. Since neither the clinical manifestations nor the morphologic features of inflammatory bowel disease are pathognomonic alone, the differential diagnosis to consider is relatively broad, and it relies on the synthesis of clinical, endoscopic, and microscopic features. Long-held histologic diagnostic principles include recognizing structural and inflammatory features of chronicity, that is, architectural distortion, basal plasmacytosis, and expansion of the lamina propria lymphoplasmacytic infiltrate. In addition, evaluation of the neutrophilic inflammation and related crypt and epithelial destruction is essential to gauge the activity of the disease. Nevertheless, these features can be difficult to confirm in special settings, including at the inception of the disease or in partially treated cases. This review will explore the classic morphologic features of ulcerative colitis and Crohn disease, followed by a detailed discussion of atypical and diagnostically challenging presentations and a brief review of the clinical aspects necessary for the daily practice of pathologists.